Synthesis of Novel Fluorescent Stilbenenitrones via a Mild, Ligand-Free Heck-Type Reaction of (E)-[4-(1,3-Dioxolan-2-yl)styryl]trimethylsilane with Benzene Diazonium Tetrafluoroborate Derivatives - Karbach, André; Stemler, Tobias; Kopp, Christian; Trommer, Wolfgang E. (Synthesis, 2014)
Nitrones are important intermediates in organic syntheses. As spin traps they allow for trapping of short-lived radicals, mainly reactive oxygen species (ROS), under formation of relatively stable nitroxides. Fluorescent nitrones also offer the possibility to follow the formation of ROS with subcellular resolution. To this end, particularly stilbenenitrones have been employed. Here, we describe the synthesis of a series of stilbenenitrones from aldehyde precursors prepared by an optimized, mild Heck-type reaction. Rather unstable benzene diazonium salts required special conditions for the trans-selective reaction with styrylsilanes. Moreover, a new method was developed to produce stilbenenitrones quantitatively in most cases. Ab initio methods were used to clarify an anomaly with respect to absorption behavior.
Keywords: ROS; spin traps; diazonium salts; nitrones; Heck reaction